Technical Guidance on Making Small Pond Geomembrane Shrimp Ponds in Bades Village, Lumajang - Irsyam, Mahrus; Djamali, R. Abdoel; Dwiyanti, Inayatus Nur; Indarto, Indarto; Subagio, Achmad; Piluharto, Bambang (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2023)
Cultivating vannamei shrimp has dominated fishery sectors and led to aquaculture development to enhance the Indonesian economy. Lumajang, specifically Bades Village, is one of the potential regions in Jawa Timur for improving fishery products because of its long shoreline of approximately 75km. Developing shrimp cultivation requires vast funds, intensive pond systems, and broad markets. Consequently, a large number of vannamei shrimp cultivation is controlled by a large company, which will supersede the role of traditional or local fishermen. This program utilizes two main methods: socializing about the opportunity of production, cultivation, and building a business entity of vannamei shrimp and practicing creating a small pond using geomembrane as a natural insulator. These activities intend to significantly increase the interest and enthusiasm of fishermen to develop vannamei small pond systems as a solution for economic independence and new income sources. As a result, a local fishing group, widely known as Mina Dampar as a partner, accepted and approved those programs implemented in their region in a 2000m2 land area.